Meanjin ([University of Melbourne], 1977)
Meanjin is a quarterly literary journal publishing the best new writing from established voices and emerging talents. For over 70 years Meanjin has articulated questions of national importance, questions or art, culture, policy and identity, as well as introducing some of the greatest literary names Australia has ever produced.